Drawing people : the human figure in contemporary art - Malbert, Roger (London : Thames and Hudson, 2015)
The act of drawing has long been considered the foundation of an artistic education, and the life class essential to the formation of an artist's style and technique. Yet in the contemporary art world drawing is increasingly regarded as a medium in its own right, and the figure as a subject for ongoing exploration well beyond the sketchbook. Featuring an international roster of over seventy artists working with pencil, ink, crayon, watercolour and charcoal, 'Drawing people' brings to life one of the most creatively rich and emotionally powerful forms of art being made today. An introduction places the medium of drawing in its historical context, discussing its intersection with photography, painting, collage and illustration. Five chapters -- 'Body', 'Self', 'Personal lives', 'Social reality' and 'Fictions' -- include short introductions outlining each theme, followed by commentaries on individual artists exploring their style, ideas and techniques, accompanied by finely reproduced images of their recent work.
boek